Integration of Raman spectroscopy and machine learning for species-specific assessment of fish freshness with insights into biogenic amines - Yuxin Zhang; Xinping Lin; Sufang Zhang; Ningbo Qin; Chaofan Ji (Food Control, 2026)

Controlling nitrosamine accumulation in dry fermented sausages using Lacticaseibacillus rhamnosus H7: The role of physicochemical drivers and precursor depletion - Ying Yue; Ning Zhao; Bingrui Guo; Jing Lv; Xin Nie; Sufang Zhang; Yingxi Chen; Beiwei Zhu; Shengjie Li; Xinping Lin (Food Microbiology, 2026)

Effect of Levilactobacillus brevis and Limosilactobacillus fermentum combined with carrot powder on the quality, safety, and microbial community of dry-fermented sausages - Siqi Zhang; Shimiao Wang; Xianhao Zhang; Hao Shang; Ying Yue; Bingrui Guo; Zhiping Zhao; Shengjie Li; Xinping Lin (Food Bioscience, 2026)

Green-engineered superhydrophobic and photothermal CuO nanofiber membranes for solar-assisted membrane distillation - Jiaxin Guo; Shangzhen Xie; Jiawei Sun; Pengfei Lin; Xinping He; Zhenyao Wang; Chunhai Yi; Alicia Kyoungjin An (Desalination, 2026)

Microbial and Flavor-Related Metabolic Changes in Sour Meat Inoculated with Saccharomyces cerevisiae LXPSC1: An Integrated Multi-omics Study - Shimiao Wang; Siqi Zhang; Jing Lv; Xianhao Zhang; Yiyao Wang; Ying Shi; Yingxi Chen; Xinping Lin (Food Bioscience, 2026)

Co-fermentation of kombucha-derived yeasts and Komagataeibacter hansenii: Effects on polyphenol composition and flavor profiles - Yanjun Wei; Yingxi Chen; Yiwei Dai; Xinping Lin; Beiwei Zhu; Chaofan Ji (Food Bioscience, 2026)

PTPRO Governs Synaptic Density, Long-Term Potentiation and Cognitive Function In Vivo - Xiangdong Wang; Jiaguo Wu; Mengna Liu; Kun Zhang; Xinping Yuan; Fangting Xing; Wenjie Xu; Yulin Zheng; Yifei Wu; Lin Luo; Xinyi Ding; Ge Gao; et al. (Neuroscience Bulletin, 2026)

Divergent impacts of additives on biological risks associated with antibiotic resistance genes during black soldier fly manure composting: A comparative study of biochar, humic acid, and tea residue amendments - Nanyi Wang; Tingzhen Xu; Wenjuan He; Genyi Wu; Xinping Li; Xiaomei Yang; Hongmei Yin; Lin Luo; Lihua Zhang; Liuqin He; Anwei Chen; Man Yu; et al. (Journal of Hazardous Materials, 2026)

Genomic insights into high GABA production by Levilactobacillus brevis Q3–11 and its application in developing functional kiwifruit juice - Bingrui Guo; Qi Wu; Xu Yan; Wei Ji; Shufeng Yin; Sufang Zhang; Yiwei Dai; Xiangyu Sun; Tingting Ma; Xinping Lin (International Journal of Food Microbiology, 2026)

Effects of partial KCl substitution for NaCl combined with LAB inoculation on the overall quality of Chouguiyu: A study based on safety, bacterial community structure, and flavor characteristics - Xiaohan Jia; Qixuan Pei; Bingrui Guo; Ning Zhao; Ying Yue; Hao Liu; Wei Ji; Shimiao Wang; Xianhao Zhang; Yingxi Chen; Ningbo Qin; Xinping Lin (Food Research International, 2026)

RNA-binding protein TARDBP enhances NPTX1 stability to induce neuronal injury and diabetic cognitive impairment - GuiTing Liu; XiaoXuan Qi; SiOu Li; XinPing Wang; TingYuan Han; LingJia Cui; HuiYing Yue; Feng Liu; Ying Lin (Molecular & Cellular Toxicology, 2026)

Fermented fruit drinks: an overview on microbial component, sensorial attributes, health benefits, and development directions on starters - Yiwei Dai; Yihui Tang; Yingxi Chen; Sufang Zhang; Xinping Lin; Chaofan Ji (Critical Reviews in Food Science and Nutrition, 2026)

Improving the quality and safety of fermented mandarin fish (Siniperca chuatsi) by co-inoculation with Latilactobacillus sakei A20 and Lactiplantibacillus plantarum LJ1–1 - Shufeng Yin; Bingrui Guo; Wenqing Wang; Wei Ji; Siqi Zhang; Changlei Ji; Chaofan Ji; Yiwei Dai; Sufang Zhang; Xinping Lin (Food Research International, 2026)

Rhodotorula mucilaginosa SY-AN-9 as a novel starter culture for improving the safety of Northeastern Chinese dried sausage: Mitigating N-nitrosamines and elucidating the underlying mechanism - Ying Yue; Xu Yan; Siqi Zhang; Yining Tang; Wei Ji; Chaofan Ji; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Chemistry, 2026)

Antioxidant strategies and mechanisms of cider fermentation with ergothioneine- and glutathione-producing yeasts: an alternative to sulfur dioxide - Naihui Dong; Yisong Jia; Kexin Xiong; Zhijie Li; Yiwei Dai; Chaofan Ji; Yingxi Chen; Xinping Lin; Sufang Zhang (Food Bioscience, 2026)

Microbial community steering via lactic acid bacteria-yeast co-inoculation: Developing a safety control strategy against nitrosamines and their precursors in Northeastern Chinese dried sausages - Ying Yue; Xu Yan; Bingrui Guo; Yiyao Wang; Siqi Zhang; Chaofan Ji; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Research International, 2026)

Dynamic changes in volatile organic compounds and microbial community of snakehead segments coated with a gallic acid–embedded edible film - Hongyu Jiang; Wang Li; Haonan Gong; Enhao Yao; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Research International, 2026)

Moderate fermentation contributes to favorable flavor and quality: Insights from full-length 16S rRNA sequencing analysis of different brands of Chouguiyu - Hao Liu; Xu Yan; Ying Yue; Shufeng Yin; Ning Zhao; Chaofan Ji; Yingxi Chen; Sufang Zhang; Yiwei Dai; Xinping Lin (Food Bioscience, 2026)

Chitosan-modified photocrosslinked silk fibroin hydrogels loaded with RA-loaded self-assembled bilayer nanoparticles promote healing of infected wounds - Zheng Sun; Linna Wang; Ye Peng; Dixin Xing; Yining Wang; Sufang Zhang; Chaofan Ji; Xinping Lin; Fengming Dong; Ningbo Qin (Chemical Engineering Journal, 2026)

Menaquinone-7 enhancement, coordinated control of biogenic amines, and flavor modulation in natto: Development of a food safety-oriented fermentation strategy - Hui Guo; Jie Hao; Yujiao Zhang; Yiwei Dai; Yingxi Chen; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Control, 2026)

An Integrated Stratigraphy Study of a Paralic Lacustrine Basin: Insights into the Organic Matter Accumulation - Meizhou Zhang; Xiaomin Zhu; Wenming Ji; Lei Ye; Xinping Zhou; Hongkui Chen; Xingyue Lin; Mianmo Meng (Journal of Marine Science and Engineering, 2026)
Several shale oil intervals, including those in offshore China, were deposited in paralic lacustrine basins that experienced marine incursions. Marine incursions could be either favorable or unfavorable for the accumulation of organic matter (OM) and shale oil. However, the influence and specific mechanisms of seawater on OM accumulation require further in-depth investigation. During the deposition of the Triassic Chang 7 Member in the Ordos Basin, seawater from the Paleo-Tethys Ocean intruded into the basin. Taking this interval as a case study, this paper employs comprehensive analyses to reveal the influence of marine incursion on water column conditions and OM accumulation. Under humid climatic conditions, the water body was fresh to brackish, characterized by high productivity and oxic–dysoxic conditions. The OM is primarily derived from algae, and its accumulation was jointly controlled by primary productivity, redox conditions, and terrigenous input. OM accumulation is controlled by fluctuations in the relative water level (RWL) associated with third-order sequences. During the period of high RWL, seawater incursions enhanced water column productivity and reduced conditions by increasing nutrient supply and salinity, resulting in the highest OM content. During the early and late periods of the RWL, as seawater receded, OM production declined while consumption and dilution increased, resulting in a gradual decrease in its content. The RWL fluctuations at the fourth-order scale also significantly influence OM accumulation. These results can enhance the understanding of OM accumulation in paralic lacustrine basins with a history of seawater incursion. While promoting shale oil exploration in the Ordos Basin, they can also serve as a research analog for shale oil exploration in basins with similar geological backgrounds, such as the Bohai Bay Basin.

Forecasting and comparative analysis of urban economic resilience in the Yangtze River Delta: An integrated CRITIC-GRA-TOPSIS and grey time-delay modeling approach - Qi Ding; Xinping Xiao; Zhaohu Wang; Lin Luo (Environment, Development and Sustainability, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Exploring the effects of different ratio of Lactococcus lactis M10 and Weissella cibaria M3 on the microbial community, quality and safety of fermented fish - Changlei Ji; Qixuan Pei; Shimiao Wang; Ning Zhao; Siqi Zhang; Sufang Zhang; Chaofan Ji; Yiwei Dai; Xinping Lin (Food Research International, 2026)

Microbial interactions and sequential inoculation of Metschnikowia koreensis and Saccharomyces cerevisiae shape cider flavor development - Yuening Li; Huipeng Liang; Yuzheng Wu; Xinping Lin; Yiwei Dai; Chaofan Ji (Food Bioscience, 2026)

Organic phosphorus strategy combining target crops and the environment to advance food production and reduce agricultural phosphorus loss - Zheng Li; Shanshan Jiang; Xuanjing Chen; Yubin Zhang; Ning Cao; Xinglin Du; Liyuan Hou; Yi Zhang; Xiaoli Wang; Dayong Guo; Xinping Chen; Lin Ma; et al. (Agriculture, Ecosystems & Environment, 2026)

Microbial succession and changes of nutritional components, volatile compounds of Chouguiyu, traditional Chinese fermented fish - Bingrui Guo; Qixuan Pei; Liting Mao; Wei Ji; Siqi Zhang; Shimiao Wang; Chaofan Ji; Sufang Zhang; Xinping Lin (Food Research International, 2025)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

Improving soy sauce quality via co-fermentation with indigenous Tetragenococcus: Reducing biogenic amines and enhancing flavor - Shiyu Wu; Zhenxiao Sun; Jian Guo; Dongmei Li; Xinping Lin; Sufang Zhang; Chaofan Ji (Food Research International, 2025)

Pectinase from Bacillus velezensis W6: A low pectin-methylesterase activity pectinase for enhancing quality and safety in Orah Mandarin wine and its mechanism for methanol reduction - Yonggang Du; Yuxuanwen Zhao; Xiaohan Wei; Yujiao Zhang; Yiwei Dai; Yingxi Chen; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Bioscience, 2025)

Integrated transcriptome and proteome analysis unveils black tea polyphenols metabolic pathways in Saccharomyces cerevisiae - Yanjun Wei; Yingxi Chen; Xinping Lin; Sufang Zhang; Beiwei Zhu; Chaofan Ji (Food Microbiology, 2025)

Insights into the balance of safety, flavor, and texture in fermented fish: A study based on full-length sequencing of fermented largemouth bass (Micropterus salmoides) - Xianhao Zhang; Bingrui Guo; Bing Dai; Shimiao Wang; Siqi Zhang; Sufang Zhang; Chaofan Ji; Beiwei Zhu; Xinping Lin (International Journal of Food Microbiology, 2025)

A leader-follower contrastive learning framework for imbalanced multimodal remote sensing image classification - Jia Li; Lin Zhao; Ping Tan; Minhui Zhao; Guoyun Zhang; Xinping Li (International Journal of Remote Sensing, 2025)

Binding modes and in vitro digestion profiles of an iron-binding peptide (EEEWDRE) derived from fermented scallop skirts - Xu Yan; Ying Yue; Bingrui Guo; Jing Lv; Yiwei Dai; Yingxi Chen; Chaofan Ji; Sufang Zhang; Beiwei Zhu; Xinping Lin (Food Chemistry, 2025)

Corrigendum to “Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis” [Toxicology and applied Pharmacology, 2023, 462:116415] - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2025)

Flavour enhancement of dry fermented sausages by nitrite-degrading Levilactobacillus brevis CHOL1: Combining flavouromics and lipidomics to elucidate the mechanism of aroma formation - Ying Yue; Ning Zhao; Shufeng Yin; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Chemistry, 2025)

Quality assessment and microbial community succession of finely chopped common carp (Cyprinus carpio) under low-temperature storage: Implications for nutritional composition and spoilage indicators - Haonan Gong; Binchen Wang; Hongyu Jiang; Wang Li; Yujiao Zhang; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Control, 2025)

A Simple Fluorescent Probe for Biothiols Detection and Imaging of Living Cells In Vivo Based on a Hemicyanine Derivative - Xia Gao; Xuehan Liu; Xinping Zheng; Yaxin Liu; Jinming Lin; Pengbo Zhang (Journal of Fluorescence, 2025)

Binding mechanism, digestive stability, and cellular interactions of a potential organic Iron supplement: Fermented scallop skirt peptide (DDDHPGIF)-Iron complex - Xu Yan; Qi Wu; Qixuan Pei; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Research International, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Effect of oxidation on finely segmented products of snakehead: Digestibility and microstructure - Hongyu Jiang; Wang Li; Haonan Gong; Chaofan Ji; Xinping Lin; Beiwei Zhu; Sufang Zhang (Food Chemistry, 2025)

Effect of co-fermentation of Rhodotorula mucilaginosa with Saccharomyces cerevisiae on the quality and flavor profile of cider - Shijiao Liu; Ruipeng Wang; Yunong Zhang; Yiwei Dai; Sufang Zhang; Xinping Lin; Chaofan Ji; Huipeng Liang; Yingxi Chen (Food Bioscience, 2025)

Lactiplantibacillus plantarum A72 inoculation enhances Citrus juice quality: A systematic analysis of the strain's fermentation properties, antioxidant capacities, and transcriptome pathways - Qi Wu; Sibo Zou; Xu Yan; Ying Yue; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Xinping Lin (Food Bioscience, 2025)

Precision-engineered bacterial nanovectors for synergetic co-delivery to harness cellular senescence and immunomodulation for enhanced tumor eradication - Zixuan Ye; Yuanzhuo Zhou; Lizhen Liang; Jiahui Zhao; Wenzheng Liu; Lingtong Meng; He Huang; Jingpeng Yang; Xinping Lin; Yanan Li (Chemical Engineering Journal, 2025)

Exploring the synergistic effect of Lactiplantibacillus plantarum 1–24-LJ and lipase on improving Quality, Flavor, and safety of Suanzharou - Qixuan Pei; Bingrui Guo; Ying Yue; Xianhao Zhang; Sufang Zhang; Chaofan Ji; Ilario Ferrocino; Luca Cocolin; Xinping Lin (Food Research International, 2025)

Enhanced torularhodin production in Rhodosporidium toruloides A1-15 under salt stress: Insights from multi-omics analysis - Mengyang Liu; Hao Liu; Wenxin Xiang; Yiwei Dai; Sufang Zhang; Chaofan Ji; Beiwei Zhu; Haitao Wang; Xinping Lin (Food Bioscience, 2025)

Anaerobic digestion and biochar/hydrochar enhancement of antibiotic-containing wastewater: Current situation, mechanism and future prospects - Yuanyi Zhao; Junguo He; Heliang Pang; Lin Li; Xinxin Cui; Yunlong Liu; Weixun Jiang; Xinping Liu (Environmental Research, 2025)

Excessive accumulation of auxin inhibits protocorm development during germination of Paphiopedilum spicerianum - Yefei Li; Hong Chen; Xinping Kong; Yuying Yin; Ji Li; Kunlin Wu; Songjun Zeng; Lin Fang (Plant Cell Reports, 2025)

Mathematical modeling and comparative metabolomics analyses of interactions between Lactiplantibacillus plantarum and Morganella morganii - Jing Han; Binkun Liu; Xinping Lin; Sufang Zhang; Liang Dong; Chaofan Ji (Food Research International, 2024)

Hydrophobic C60-modified PVDF membrane with micro-nano structures for mitigating CaSO4 scaling in direct contact membrane distillation (DCMD) - Xiaoju Yan; Xinping Lin; Cong Ma; Chengyu Yang; Tianqi Xing (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of saturated aldehyde oxidation: A DFT insight into volatiles forming from decanal thermal oxidation - Binchen Wang; Shaohua Dou; Shang Wang; Yi Wang; Sufang Zhang; Xinping Lin; Chaofan Ji; Liang Dong (Food Chemistry, 2024)

Improving natto quality through Co-fermentation of functionally complementary Bacillus and Lactiplantibacillus species - Xiaoxu Ren; Xiaofu Wang; Xinping Lin; Sufang Zhang; Chaofan Ji (Food Bioscience, 2024)

Novel microbial fermentation for the preparation of iron-chelating scallop skirts peptides-its profile, identification, and possible binding mode - Xu Yan; Ying Yue; Bingrui Guo; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Liang Dong; Beiwei Zhu; Xinping Lin (Food Chemistry, 2024)

Ternary stabilization strategies for succinonitrile-based in situ polymerized electrolyte enabling high-performance solid lithium metal batteries - Chenyu Lin; Tianqi Yang; Haiyuan Zhang; Donghuang Wang; Wenkui Zhang; Yao Wang; Yang Xia; Hui Huang; Xinhui Xia; Yongping Gan; Xinping He; Xinyong Tao; et al. (Chemical Engineering Journal, 2024)

The effects of Lactiplantibacillus plantarum 3-19 and Pediococcus pentosaceus 18-1 on preventing the accumulation of biogenic amines and promoting the production of volatile organic compounds during sour meat fermentation - Hao Shang; Ying Yue; Bingrui Guo; Chaofan Ji; Sufang Zhang; Liang Dong; Ilario Ferrocino; Luca Simone Cocolin; Xinping Lin (International Journal of Food Microbiology, 2024)

Effects of quercetin- and Lactiplantibacillus plantarum-containing bioactive films on physicochemical properties and microbial safety of grass carp - Zuoli Zhang; Xianhao Zhang; Yao Li; Wentao Su; Qian Xu; Sufang Zhang; Huipeng Liang; Chaofan Ji; Xinping Lin (Food Chemistry, 2024)

Monitoring the yeasts ecology and volatiles profile throughout the spontaneous fermentation of Taggiasca cv. table olives through culture-dependent and independent methods - Chiara Traina; Ilario Ferrocino; Ambra Bonciolini; Vladimiro Cardenia; Xinping Lin; Kalliopi Rantsiou; Luca Cocolin (International Journal of Food Microbiology, 2024)

Metabolic profiling of wort fermented with water kefir grains and its effect on wort quality - Shuyao Wen; Naihui Dong; Yujiao Zhang; Bo Yang; Binchen Wang; Yiwei Dai; Xinping Lin; Liang Dong; Sufang Zhang (Food Bioscience, 2024)

Flavor profile and quality of strawberry wine are improved through sequential fermentation with indigenous non-Saccharomyces yeasts and Saccharomyces cerevisiae - Bo Yang; Shijiao Liu; Hongwen Zang; Yiwei Dai; Sufang Zhang; Xinping Lin; Huipeng Liang; Yingxi Chen (Food Bioscience, 2024)

Excellent iron-chelating capacity of Yesso scallop (Patinopecten yessoensis) skirt hydrolysate fermented by Bacillus subtilis M17-b7 - Xu Yan; Ying Yue; Qixuan Pei; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Liang Dong; Beiwei Zhu; Xinping Lin (Food Bioscience, 2024)

Intelligent agent for hyperspectral image classification with noisy labels: a deep reinforcement learning framework - Chunhua Fang; Guifeng Zhang; Jia Li; Xinping Li; Tengfei Chen; Lin Zhao (International Journal of Remote Sensing, 2024)

Investigating mechanism of enhanced anti-fouling performance of MXene modified Janus MD membrane by XDLVO theory combined with surface elemental integration method - Chengyu Yang; Xiaoju Yan; Cong Ma; Xinping Lin; ChengZhi Yao; XueYan Li (Process Safety and Environmental Protection, 2024)

Transmission characteristics and the factors influencing stable oxygen isotopes in precipitation, soil water, and drip water in Remi Cave, Western Hunan, China - Yiping Tian; Yunxia Li; Jiayan Li; Chenxi Yang; Angli Du; Miaofa Li; Xinping Zhang; Lin Zhao; Lidan Liu; Zhiguo Rao (Journal of Hydrology, 2024)

Inoculation of Yarrowia lipolytica promotes the growth of lactic acid bacteria, Debaryomyces udenii and the formation of ethyl esters in sour meat - Bingrui Guo; Qi Wu; Cuicui Jiang; Yingxi Chen; Yiwei Dai; Chaofan Ji; Sufang Zhang; Liang Dong; Huipeng Liang; Xinping Lin (Food Microbiology, 2024)

Optimizing phosphorus fertilizer use to enhance water quality, food security and social equality - Zhaohai Bai; Ling Liu; Carolien Kroeze; Maryna Strokal; Xinping Chen; Zengwei Yuan; Lin Ma (Resources, Conservation and Recycling, 2024)

Evolution of vegetation cover and impacts of climate change and human activities in arid regions of Northwest China: a Mu Us Sandy Land case - Jing Lin; Wenhao Bo; Xinping Dong; Ruiwan Zhang; Junping Yan; Tao Chen (Environment, Development and Sustainability, 2024)

Supplement of food functional factor ergothioneine can effectively prevent liver injury in mice - Kexin Xiong; Hui Guo; Yisong Jia; Yueqi Liang; Bo Yang; Yingxi Chen; Xinping Lin; Sufang Zhang (Food Bioscience, 2024)

Rapid visual nucleic acid detection of Vibrio alginolyticus by recombinase polymerase amplification combined with CRISPR/Cas13a - Yanan Wang; Yachao Hou; Xinping Liu; Na Lin; Youyou Dong; Fei Liu; Wenrong Xia; Yongqi Zhao; Weiwei Xing; Jin Chen; Changguo Chen (World Journal of Microbiology and Biotechnology, 2024)

Coupling the measures of pollution source control and water replenishment to improve water quality in the catchment scale of Qianshan River Basin - Cheng Gao; Zhantuo Xu; Xiaoju Yan; Guodong Wang; Xinping Lin; Jichen Zhang; Xin Guo (Environmental Pollution, 2024)

Deep exploration of lipid oxidation into flavor compounds: A density functional theory study on (E)-2-decenal thermal oxidative reaction - Binchen Wang; Shang Wang; Yi Wang; Sufang Zhang; Xinping Lin; Xianbing Xu; Chaofan Ji; Huipeng Liang; Liang Dong (Food Chemistry, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Surface oxygenation of non-oxide boosts oxidation activity on polyoxometalate subunits: An enhanced Venus flytrap mechanism - Youwei Sun; Wenyu Long; Jian zhang; Yanjuan Wang; Shaozheng Hu; Yixin Lian; Weizhou Jiao; Ruixin Wang; Yazhou Zhang; Haiqiang Lin; Xinping Duan (Chemical Engineering Journal, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Ergothioneine yield of Rhodotorula species positively correlated with hydrogen peroxide tolerance - Kexin Xiong; Naihui Dong; Bo Yang; Yingxi Chen; Huipeng Liang; Xinping Lin; Sufang Zhang (Food Bioscience, 2023)

High-speed electrospinning of phycocyanin and probiotics complex nanofibrous with higher probiotic activity and antioxidation - Zuoli Zhang; Wentao Su; Yao Li; Sufang Zhang; Huipeng Liang; Chaofan Ji; Xinping Lin (Food Research International, 2023)

Isopimaric acid, an ion channel regulator, regulates calcium and oxidative phosphorylation pathways to inhibit breast cancer proliferation and metastasis - Jiacheng Li; Xiaozhen Liu; Lin Chen; Xinping Zhu; Zhihong Yu; Liyao Dong; Xinyun Zhao; Hongling Zou; Qin Wei; Yongcai Feng; Yongqiang Zhu; Kequn Chai; et al. (Toxicology and Applied Pharmacology, 2023)

Effect of Saccharomyces cerevisiae LXPSC1 on microorganisms and metabolites of sour meat during the fermentation - Jing Lv; Xinping Lin; Mengyang Liu; Xu Yan; Huipeng Liang; Chaofan Ji; Shengjie Li; Sufang Zhang; Yingxi Chen; Beiwei Zhu (Food Chemistry, 2023)

Microbial metabolic transformation and antioxidant activity evaluation of polyphenols in kombucha - Shengyang Shi; Yanjun Wei; Xinping Lin; Huipeng Liang; Sufang Zhang; Yingxi Chen; Liang Dong; Chaofan Ji (Food Bioscience, 2023)

Identifying the activity origin of silver catalysts induced by interfacial electron localization for regioselective C O bond hydrogenation - Jinglin Zou; Xinping Duan; Xu Liu; Lele Huang; Xiaoying Liu; Jiachang Zuo; Weizhou Jiao; Haiqiang Lin; Linmin Ye; Youzhu Yuan (Chemical Engineering Journal, 2023)

Coastal Protection by Planted Mangrove Forest during Typhoon Mangkhut - Xiaoxia Zhang; Pengzhi Lin; Xinping Chen (Journal of Marine Science and Engineering, 2022)
Mangroves provide many ecosystem services, including coastal protection against storm surges and waves. As an adaptive method for coastal defense, mangroves were widely restored and planted in tropical and subtropical regions, such as the coastal regions in Southeast Asia. Field surveys were conducted to quantify the nature-based coastal protection provided by a planted mangrove forest along the coasts of Shanwei, Guangdong Province, China, under typhoon influence. The resilience of mangrove trees was assessed under the impact of Typhoon Mangkhut (2018), which induced a maximum storm surge of 1.74 m with a maximum wave height of 1.16 m in the study area. The pre- and post-typhoon surveys and hydrodynamic measurements were conducted at a mudflat with planted mangroves. The wave height reduction reached 77% over 100 m wide mangrove forest. Our results suggest that a six-year-old planted mangrove forest with a ~100 m width might withstand a super typhoon impact and provide substantial protection for the fish ponds and embankments behind the mangrove forest. No uproots or deadly breakage of stems were observed in the mangrove forest, while severe defoliation was spotted for a small portion of trees in the study area, mainly along the wind path, the windward edge of the forest, and among the taller plants. Obvious sedimentation in the mangrove front and the tidal flat was observed during the typhoon Mangkhut (2018) and the entire typhoon season of 2018.

Kidney function change after transcatheter aortic valve replacement in patients with diabetes and/or hypertension - Jiaqi Fan; Changjie Yu; Kaida Ren; Wanbing Lin; Stella Ng; Zexin Chen; Xinping Lin; Lihan Wang; Qifeng Zhu; Yuxin He; Jubo Jiang; Xianbao Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Wave Attenuation by Spartina alterniflora under Macro-Tidal and Storm Surge Conditions - Xiaoxia Zhang; Pengzhi Lin; Zelin Gong; Bing Li; Xinping Chen (Wetlands, 2020)

Effects of Temperature on Bacterial Biodiversity and Qualities of Fermented Yucha Products - Shuai Wang; Jing Han; Jingbo Zhang; Xinping Lin; Huipeng Liang; Shengjie Li; Xiuping Dong; Chaofan Ji (Journal of Aquatic Food Product Technology, 2020)

Discovery of a virus of the species Enterovirus F in goats - Xiaoran Chang; Qian Lin; Junying Hu; Xu Wang; Xin Li; Menglu Cai; Weiyu Wang; Zecai Zhang; Xinping Wang (Archives of Virology, 2019)

Homologous gene targeting of a carotenoids biosynthetic gene in Rhodosporidium toruloides by Agrobacterium-mediated transformation - Wenyi Sun; Xiaobing Yang; Xueying Wang; Xinping Lin; Yanan Wang; Sufang Zhang; Yushi Luan; Zongbao K. Zhao (Biotechnology Letters, 2017)

RKIP Regulates Neural Cell Apoptosis Induced by Exposure to Microwave Radiation Partly Through the MEK/ERK/CREB Pathway - Hongyan Zuo; Tao Lin; Dewen Wang; Ruiyun Peng; Shuiming Wang; Yabing Gao; Xinping Xu; Li Zhao; Shaoxia Wang; Zhentao Su (Molecular Neurobiology, 2015)

The Effect of EPO Gene Overexpression on Proliferation and Migration of Mouse Bone Marrow-Derived Mesenchymal Stem Cells - Haihong Lin; Xinping Luo; Bo Jin; Haiming Shi; Hui Gong (Cell Biochemistry and Biophysics, 2015)